MILITARY AND PROFESSIONAL TRAINING OF RESERVE OFFICERS IN THE WORLD LEADING COUNTRIES - Yaroslav Zoriy (Vasyl Stefanyk Precarpathian National University, 2018)
The article delves into the problem of different approaches to organizing military training and educating of students/civilians in compliance with the program of reserve officers in the leading countries of the world. It is disclosed that the military and political leadership of foreign countries, especially member-states of NATO, institutions to educate their up-and-coming leadership. Noteworthy, the in-depth analysis indicated that world leading countries' military institutions designed the programs to train students intellectually, physically and psychologically to grow into the future leaders of the certain Motherland. Primarily, it concerns the unification and improvement of the functioning of the existing systems of training and re-training of officers. Potential officers undergo grueling physical training to develop the combat qualities essential for the armed forces to maintain an environment where cadets develop courage, discipline, integrity, honor, dignity and patriotism. The top priority of training reserve officers is protect and defense their sovereignty and territorial integrity. According to US military experts, reserves are the main source of meeting the needs of troops in the personnel and significantly increases their combat capability. US Reserve Officers are assigned roles and missions to provide combat and support forces trained for wartime, and capable of providing peacetime domestic emergency assistance. To be more precise, the principal mission of the Army Reserve is to provide wartime combat service support (CSS) and a portion of the Army's combat support (CS).Noteworthy, the historical and methodological analysis confirmed the feasibility of emulating the experience of foreign Armed Forces in preparing this category of students/civilians for military-related activities.  Simultaneously, the study highlights the contradictory aspects of Ukrainian modern military training and educating system, involving the ongoing JFO participation of the units of the Armed Forces of Ukraine in the east of the state. The results of comparative analysis of the quality of military education in the leading countries of the world provide an opportunity to consider the system of military education of Ukraine from different points of view, and, therefore, to more objectively substantiate the factors that determine its effectiveness and quality. In addition, taking into account the factors that determine the qualitative characteristics of military education systems in foreign countries in many ways contribute to the formation of perspective guidelines for improving the quality of professional training of the Armed Forces of Ukraine. Key words: military training and education; reserve officers; military-related activity; Armed Forces of the world leading countries.